2016
DOI: 10.1007/s00181-015-1057-1
|View full text |Cite
|
Sign up to set email alerts
|

Correlation structure and principal components in the global crude oil market

Abstract: This article investigates the correlation structure of the global crude oil market using the daily returns of 71 oil price time series across the world from 1992 to 2012. We identify from the correlation matrix six clusters of time series exhibiting evident geographical traits, which supports Weiner (1991)'s regionalization hypothesis of the global oil market. We find that intra-cluster pairs of time series are highly correlated while inter-cluster pairs have relatively low correlations. Principal component an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…There are a few components whose magnitudes are significantly greater than the averages. However, we did not observe solid evidence that the correlations of the corresponding return time series of these components are among the largest, which is different from the U.S. stock market [17] and the global crude oil market [38]. We investigated the relationship between the eigenvector components and stocks' market capitalizations.…”
Section: Belowmentioning
confidence: 77%
See 1 more Smart Citation
“…There are a few components whose magnitudes are significantly greater than the averages. However, we did not observe solid evidence that the correlations of the corresponding return time series of these components are among the largest, which is different from the U.S. stock market [17] and the global crude oil market [38]. We investigated the relationship between the eigenvector components and stocks' market capitalizations.…”
Section: Belowmentioning
confidence: 77%
“…The characteristic of a market effect is the eigenvector u 1 of the largest eigenvalue λ 1 has roughly equal components on all of the N stocks, showing a nice linear relationship between the returns of the eigenportfolio constructed from u 1 and of the market index [17]. Usually, other deviating eigenvalues do not reflect a market effect but the comovement of stocks in the same industrial sector [17], the same traits shared by stocks [34], or geographic localization [38]. However, it is also possible that other deviating eigenvalues also reflect a market effect, such as the USA housing market [18].…”
Section: Belowmentioning
confidence: 99%
“…Indeed, the oil return risks could inhibit current investment for crude oil [5]. Changes in market stability have considerable impacts on economy [14][15][16][17][18]. First, changes in crude oil return risks essentially impact decisions made by market participants, such as oil producers, consumers, and policy makers.…”
Section: Opecmentioning
confidence: 99%
“…Kenett et al (2010) constructed a network using the partial correlation coefficient method as a global equity information and found that the financial sector, particularly the investment services, is the most influential stock. Zhou, Mu, and Kertész (2012), Meng et al (2014), Meng, Xie, and Zhou (2015), Qian et al (2015), and Dai, Xie, Jiang, Jiang, and Zhou (2016) used the stochastic matrix method as the global equity information and analysed its structural characteristics. Tu (2014) used Engle-Granger two-step method to build the edge information of stock network and analysed its structural characteristics.…”
Section: Introductionmentioning
confidence: 99%